Perceptions of caregivers on immunization in Ntungamo district, Uganda - Topher, Byamukama; Margaret, Keraka; Eliphas, Gitonga (International Journal of Community Medicine and Public Health | December 2021 | Vol 8 | Issue 12 Page 5729 International Journal of Community Medicine and Public Health, 2022)
Background: Immunization is one of the most cost-effective public health interventions to reduce child mortality and morbidity associated with infectious diseases. The objective of this study was to determine the perceptions of caregivers on immunization in Ntungamo district. Methods: Quasi-experimental study was used with health centres assigned to intervention and control groups. Purposive sampling was used to select the two counties where the study was done. Proportional sampling was done to get study samples from each health facility, while systematic sampling was done to get study participants. A total of 787 children from twelve health facilities provided the study sample. A post intervention evaluation was conducted to determine the effect of these interventions. Association of variables was tested using Mann Whitney U-test and Chi-square. Results: On benefits, most caregivers in the intervention group (85.3%) and in the control group (54.3%) regarded immunization as very highly and moderately beneficial to their children respectively. On risks, most caregivers in the intervention group (85.5%) and control group (43.1%) regarded the risk factor associated with immunization as very low and moderate respectively. From hypothesis testing, there was a significant difference on the perceived benefits and risks of immunization between the intervention and control group. Conclusions: Most caregivers in the intervention and control group regarded immunization as very highly beneficial and moderately to their children respectively. Most of the caregivers in the intervention and control group regarded the risk factor associated with immunization as very low and moderate respectively.